Epidemiology of HPV genotypes in Uganda and the role of the current preventive vaccines: A systematic review - Banura, Cecily; Mirembe, Florence M; Kataoire, Anne R; Namujju, Proscovia B; Namujju, AnthonProscovia B; Mbonye, Anthony K; Wabwire, Fred M (Infectious Agents and Cancer, 2011)
Abstract Background: Limited data are available on the distribution of human papillomavirus (HPV) genotypes in the general population and in invasive cervical cancer (ICC) in Uganda. Yet, with the advent of preventive HPV vaccines that target HPV 16 and 18 responsible for causing about 70% of ICC cases in the world, such information is crucial to predict how vaccination and HPV-based screening will influence prevention of ICC. Methods: To review the distribution of HPV infection and prevalent genotypes, electronic databases (e.g. PubMed/ MEDLINE and HINARI) were searched for peer reviewed English articles on HPV infection up to November 30, 2010. Eligible studies were selected according to the following criteria: DNA-confirmed cervical or male genital HPV prevalence and genotypes, HPV incidence estimates and HPV seroprevalence among participants. Results: Twenty studies were included in the review. Among HIV negative adult women, the prevalence of HR-HPV infections ranged from 10.2% -40.0% compared to 37.0% -100.0% among HIV positive women. Among HIV positive young women aged below 25 years, the prevalence of HR-HPV genotypes ranged from 41.6% -75.0% compared to 23.7% -67.1% among HIV negative women. Multiple infections with non vaccine HR-HPV genotypes were frequent in both HIV positive and HIV negative women. The main risk factors for prevalent HPV infections were age, lifetime number of sexual partners and HIV infection. Incident infections with HR-HPV genotypes were more frequent among adult HIV positive than HIV negative women estimated at 17.3 and 7.0 per 100 person-years, respectively. Similarly, incident HR-HPV among young women aged below 25 years were more frequent among HIV positive (40.0 per 100 person-years) than HIV negative women (20.3 per 100 person-years) women. The main risk factor for incident infection was HIV infection. HPV 16 and 18 were the most common genotypes in ICC with HPV 16/18 contributing up to 73.5% of cases with single infections. Among uncircumcised adult HIV positive males, HR-HPV prevalence ranged from 55.3% -76.6% compared to 38.6% -47.6% in HIV negative males. Incident and multiple HR-HPV infections were frequent in HIV positive males. Being uncircumcised was the main risk factor for both prevalent and incident HPV infection. Conclusion: Infections with HR-HPV genotypes were very common particularly among HIV positive individuals and young women irrespective of HIV status. Given the high prevalence of HIV infection, HPV-associated conditions represent a major public health burden in Uganda. However, although the most common HPV genotypes in ICC cases in Uganda were those targeted by current preventive vaccines, there were a large number of individuals infected with other HR-HPV genotypes. Technology allowing, these other HR-HPV types should be considered in the development of the next generation of vaccines
Keywords: Epidemiology; HPV genotypes; Preventive vaccines